2022
DOI: 10.3389/fphar.2022.954867
|View full text |Cite
|
Sign up to set email alerts
|

Taohong siwu decoction attenuates AIM2 and NLRC4 inflammasomes by ameliorates deoxyribonucleic acid damage after ischemic stroke

Abstract: Taohong siwu decoction (THSWD) has been shown to have a therapeutic effect on ischemic strokes (IS). However, it is not clear to us whether THSWD reduces deoxyribonucleic acid (DNA) damage after stroke and reduces the inflammatory response caused by the damage. Therefore, we constructed an IS model (I/R) in rats and performed oxygen-glucose deprivation/reoxygenation (OGD/R) on BV2 cells. Then ELISA, immunofluorescence staining, immunohistochemistry staining, and RT-qPCR were performed to detect the expressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Previously, our group identified the five major components of THSWD (gallic acid, protocatechuic acid, hydroxysafflor yellow A, amygdalin, and paeoniflorin) with the aid of UPLC-QTOF-MS [ 17 ]. In recent years, our group has made some conclusions through in vivo and in vitro experiments that THSWD can reduce inflammatory injury and nerve injury by regulating mitochondrial DNA and nuclear DNA [ 18 ], mitochondrial autophagy and activation of NLRP3 inflammatory vesicles in ischemic stroke rats [ 19 ]. In vivo, it is also confirmed that THSWD inhibits the mitochondrial autophagy-NLRP12 inflammatory body pathway of brain cells to protect brain cells from injury [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our group identified the five major components of THSWD (gallic acid, protocatechuic acid, hydroxysafflor yellow A, amygdalin, and paeoniflorin) with the aid of UPLC-QTOF-MS [ 17 ]. In recent years, our group has made some conclusions through in vivo and in vitro experiments that THSWD can reduce inflammatory injury and nerve injury by regulating mitochondrial DNA and nuclear DNA [ 18 ], mitochondrial autophagy and activation of NLRP3 inflammatory vesicles in ischemic stroke rats [ 19 ]. In vivo, it is also confirmed that THSWD inhibits the mitochondrial autophagy-NLRP12 inflammatory body pathway of brain cells to protect brain cells from injury [ 20 ].…”
Section: Introductionmentioning
confidence: 99%